2015
DOI: 10.17221/8496-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gastric dilatation and volvulus in central Europe: an internet survey

Abstract: ABSTRACT:The aim of this internet-based questionnaire was to determine risk factors for the development and survival of gastric dilatation and volvulus (GDV) in dogs in central Europe. The questionnaire focused on general information, feeding and elimination behaviour, family history, personality and routine habits, was freely distributed on the internet. Respondents were recruited by e-mail, and announcement of the survey on websites focused on dogs or breeder clubs and flyers in veterinary clinics and at dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…The literature searches uncovered six papers (Glickman et Uhrikova et al, 2015) that either partially or fully addressed the PICO question. These papers do not neatly address the PICO as the dogs studied either all/almost all were fed a kibble only diet or kibble as the primary diet (Glickman et al, 1997;Ragavan et al, 2004) or fed different diet types in combination (Theyse et al, 1998;Uhrikova et al, 2015) and/or assessed diet in terms of the maximum size of the food particles (Theyse et al, 1998;Uhrikova et al, 2015) that comprised the diet fed so the summaries of the experimental details should be examined for further understanding.…”
Section: The Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…The literature searches uncovered six papers (Glickman et Uhrikova et al, 2015) that either partially or fully addressed the PICO question. These papers do not neatly address the PICO as the dogs studied either all/almost all were fed a kibble only diet or kibble as the primary diet (Glickman et al, 1997;Ragavan et al, 2004) or fed different diet types in combination (Theyse et al, 1998;Uhrikova et al, 2015) and/or assessed diet in terms of the maximum size of the food particles (Theyse et al, 1998;Uhrikova et al, 2015) that comprised the diet fed so the summaries of the experimental details should be examined for further understanding.…”
Section: The Evidencementioning
confidence: 99%
“…One paper (Uhrikova et al, 2015) found no effect of feeding a kibble only diet, but dogs fed a diet containing some kibble were more likely to experience a GDV than dogs fed a diet with no kibble. However, in this study the median weight of the dogs in the control group was significantly different to those in the two GDV groups (groups based on GDV -survival: 1.…”
Section: The Evidencementioning
confidence: 99%
See 3 more Smart Citations